Sistem Informasi Pelayanan Posyandu Pada Kelurahan Tangki, Jakarta Barat Berbasis Android - Arroyana Firdauz, Rizky; Fauziyah; Galih Whendasmoro , Raditya (Jurnal Jaring SainTek, 2023)
Posyandu are types of activities that trying to build health of people and used for the maintenance of community. But currently the implementation of information service in posyandu are still experiencing several problem, including data on activities that still use paper so that processing activity report data takes longer, accumulated report data, as well as allowing for loss of posyandu activity data in Tangki ward West Jakarta. Based on the existing problem, a posyandu service information system was designed and built which is expected to be able to handle these problems. In defining needs and analyzing system development data collection methods were carried out by means of observation, interviews and review of literature from various sources of information. For analysis and design methods using Unified Modeling Language (UML), the posyandu service information system uses the Kotlin programming language and the database uses the MySQL database.